Czech Republic : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that economic performance of the Czech Republic strengthened during 2005-06, supported by the expanding capacity of the export-oriented automotive sector and a cyclical recovery in the European Union. The momentum of growth has been underpinned by strong productivity gains, leading to a surge in exports and further investment in the tradable goods sector. The koruna strengthened, helping to keep inflation down. Growth is projected to remain robust in 2007-08, although its momentum will slow as the effects of the recent export capacity expansion unwind.